The Socio-Economic Dynamics of the Small-House Household Structure in Harare Metropolitan Province: A Gender Perspective - Wonder Muchabaiwa (Taylor and Francis Group, 2023)
The study interrogated the socio-economic dynamics of the small-house households. The small-house relationship is a secretive long-term relationship between a married man and another woman where both develop an emotional attachment. The study was conducted in Harare metropolitan province and adopted a gender perspective to illuminate the gender dynamics and socio-economic circumstances of children growing up in small-house households. The secretive nature and complexity of the small-house household structure render the nuances of economic support in such contexts worth exploring to add value to the Sociology of Families and Households. The qualitative research study employed in-depth interviews to collect data from 36 participants who were purposively sampled. The study findings reveal that the small-house household remains a problematic context for raising children. Disengaged fatherhood tends to expose such households to poverty as the breadwinning role is left to one partner. Reportedly, disengaged fatherhood in small-house households tends to affect financial resources for food, rentals, water and electricity bills and school fees. Problems experienced in small-house households are often exacerbated by the secretive nature of the relationship. The study also reveals that conflict between partners is mainly a result of constrained financial and material resources. The small-house households may inadvertently violate children’s rights, including opportunities to access education and social security. The study recommends the expansion of the Zimbabwe Marriage Act of 1997 to acknowledge variety of relationships and enforce financial obligations on the partners to take care of the children.